Analisis Dampak Penggunaan Gadget terhadap Karakter Profil Pelajar Pancasila Siswa Kelas V SDN 70 Prabumulih - Lisnita Lisnita; Erfan Ramadhani; Ali Fakhrudin (Journal on Education, 2023)
The study alms to analyze the impact of using gadgets on the character profile of fifth grade students at SD Negeri 70 Prabumulih. The research uses descriptive qualitative research. The population in this study were fifth grade students at SD Negeri 70 Prabumulih totaling 22 students. Date collection techiques in this study are observation, interviews and documentation. Data analysis techiques are data collection, data reduction, data presentation and conclusions. The result of this study indicate that many students still use gadget to play. From this, children who intially like to play with their friends can change their habit of being given gadgets as a substitute for playmates. Thus, it is important to notify the negative impact of using gadgets.